Diverse HIV-1 escape pathways from broadly neutralizing antibody PGDM1400 in humanized mice - Yme U. van der Velden; Julien Villaudy; Esther Siteur - van Rijnstra; Cynthia A. van der Linden; Monique A. Vink; Edith E. Schermer; Kees Weijer; Ben Berkhout; Rogier W. Sanders; Marit J. van Gils (Taylor & Francis Group, 2020)
Recent studies have shown the potential of broadly neutralizing antibodies (bnAbs) for HIV-1 treatment. One of the candidate antibodies moving into clinical trials is the bnAb PGDM1400. Here, we studied the therapeutic potency and escape pathways of bnAb PGDM1400 during monovalent therapy in human immune system (HIS) mice using the BG505, REJO, MJ4 and AMC008 virus isolates. PGDM1400 administered during chronic infection caused a modest decrease in viral load in the first week of administration in 7 out of 10 animals, which correlated with the in vitro neutralization sensitivity of the viruses to PGDM1400. As expected for monotherapy, viral loads rebounded after about a week and different viral escape pathways were observed, involving the deletion of glycans in the envelope glycoprotein at positions 130 or 160. (Pre)clinical trials should reveal whether PGDM1400 is a useful component of an antibody combination treatment or as part of a tri-specific antibody.